Seeding phenology influences wood mouse seed choices: the overlooked role of timing in the foraging decisions by seed-dispersing rodents - Sunyer, Pau; Espelta, Josep Maria; Bonal, Raul; Muñoz, Alberto (Behavioral Ecology and Sociobiology, 2014)
Scatter-hoarding rodents influence the population dynamics of plants by acting as seed predators and dispersers. Therefore, rodent foraging preferences for certain seed traits (species, size, condition) have been extensively studied. However, to what extent these preferences are fixed or they track the temporal changes on seed characteristics due to phenological differences has been seldom explored.We stud- ied the temporal variability in seed preferences by wood mouse (Apodemus sylvaticus), according to phenological changes in seed characteristics of two co-occurring oaks (Quercus ilex and Quercus pubescens). The phenology of acorn abundance and the acorn predation/dispersal patterns by rodents were monitored over an entire seeding season. Results revealed temporal changes in rodent preferences for acorns of the two oaks, matching their different seeding phe- nology (earlier in Q. pubescens and later in Q. ilex). On the other hand, whatever the species considered, rodents preferred larger and sound acorns along the entire season, although the dispersal of infested ones increased slightly during the peaks of acorn drop. The observed influence of seeding phenology on seed choices by rodents warns about inferring definite conclusions regarding their foraging behavior when arising from short-term experiments. Indeed, this study reveals that foraging preferences may be highly dynamic and context- dependent for some seed traits (e.g., species and condition), rather than fixed behavioral patterns. Plasticity in rodent for- aging choices may allowthem to successfully exploit different oaks with uncoupled seeding phenologies, while potentially favoring their coexistence.
Keywords: acorn; Apodemus sylvaticus; dispersal; Quercus; seed; seed traits